Pelatihan Penyusunan Laporan Keuangan Masjid di Kelurahan Kabonena Kota Palu - Pakkawaru, Irham; Syafaat, Muhammad; Amalia, Rizki; Nuriatullah; Hidayah, Noor Riefma; Pratamasari, Dede Arseyani; Awaliyah, Nurul Qalbi; Wahyudi, Eko Albar (Rahmatan Lil 'Alamin Journal of Community Services, 2026)
Mosques, as non-profit entities, are required to be transparent and accountable in their financial management. However, the reality on the ground shows that many mosque administrators still do not understand how to prepare financial statements in accordance with applicable accounting standards. This community service activity aims to improve the understanding of mosque administrators in Kabonena Village, Palu City, in preparing financial statements. The training was held on October 1, 2025, at the Kabonena Village Office and was attended by 65 mosque administrators. The training was conducted using a combination of lectures, discussions, and hands-on practice in financial statement preparation. The effectiveness of the training was measured through pre-test and post-test assessments analyzed using the Wilcoxon Signed-Rank Test. The evaluation results showed an increase in participants' average scores from 38.46 on the pre-test to 83.38 on the post-test, with a p-value of 0.000. These findings demonstrate that the training approach applied was effective in improving mosque administrators' understanding of financial statement preparation in accordance with the principles of transparency and accountability.